Clinical correlates of positive and negative cases of appendicitis - Irfan, Syed Shahid; Gattu, E. Muniswamy (International Surgery Journal, 2016)
Background:The diagnosis of acute appendicitis is essentially clinical; however, a decision to operate based on clinical suspicion alone can lead to the removal of a normal appendix in 15-30% of cases. A number of clinical and laboratory based scoring system have been devised to assist diagnosis. Methods: A detailed history as to the method of presentation, thorough clinical examination and all patients were investigation with routine blood tests, WBC count, DC, USG abdomen and Pelvis, X-ray, blood grouping and Rh typing, and histopathological study of the appendix were performed and reported by senior pathologist of the department. Results:In the study population of 100 patients, 84 were histopathologically proved appendicitis. Among them 64 (76.2%) had raised leucocyte count and 20 (23.8%) had normal leucocyte count. Out of 16 histopathologically negative cases, 5 (31.3%) had raised leucocyte count and 11 (68.7%) had normal leucocyte count. Conclusions:Negative appendectomy rate can be decreased, if appendectomy is avoided in cases where WBC count, neutrophil count and grade compression sonography (USG) abdomen normal.